SANKSI PIDANA TERHADAP KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN HILANGNYA NYAWA ZAINAL ARIFIN (PUTUSAN NOMOR : 1346/PID.SUS/2023/PN.SBY): Criminal Sanctions for Traffic Accidents Resulting in the Loss of Zainal Arifin Life (Decision Number: 1346/Pid.Sus/2023/Pn.Sby) - Erlina Patricia; Dian Adriawan Daeng Tawang (Faculty of Law, Universitas Trisakti, 2025)
The purpose of this study is to analyze Decision Number: 1346/Pid.Sus/2023/Pn.Sby on Criminal Sanctions for Traffic Accidents Resulting in the Loss of Zainal Arifin Life. The identification problems discussed are 1) Is the provision of criminal sanctions against the defendant Caesar Rianaditya Fasa Ardiansyah Bin Djoko Purnomo which resulted in loss of life by Law Number. 22 of 2009 concerning Traffic and Transportation Roads?; and 2) Is the criminal sanction imposed by the Panel of Judges in Decision Number: 1346/Pid.Sus/2023/Pn.Sby by imposing a prison sentence of 5 (five) months by the objectives of punishment?. This research uses a type of normative legal research which is descriptive analysis, using secondary data, then processed qualitatively. This study result and oncludes that the 1) criminal sanction imposed on the defendant is very light and not optimal because it is not by the criminal sanctions in Article 310 paragraph (4) of Law Number 22 of 2009 concerning Traffic and Transportation Roads, and has not reflected a sense of justice; 2) the imposition of criminal sanctions is not by the objectives of punishment in absolute theory, relative theory, combined theory and contemporary theory.